2019
DOI: 10.1007/s00392-019-01520-z
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of transportation delay in patients with suspected ST-elevation-myocardial infarction in the VIENNA-STEMI network

Abstract: Objective The emergency medical service (EMS) provides rapid pre-hospital diagnosis and transportation in ST-elevation myocardial infarction (STEMI) systems of care. Aim of the study was to assess temporal and regional characteristics of EMS-related delays in a metropolitan STEMI network. Methods Patient call-to-arrival of EMS at site (call-to-site), transportation time from site to hospital (site-to-door), call-todoor, patient's location, month, weekday, and hour of EMS activation were recorded in 4751 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…In Iran, 24/7 primary percutaneous coronary intervention (PCI) as the standard treatment strategy for patients with ST-elevation myocardial infarction (STEMI) [3][4][5][6][7] was launched in September 2015 to achieve a fair distribution of healthcare resources. Currently, 49 general and heart hospitals provide these services, with 48 915 patients having undergone primary PCI thus far.…”
Section: Sirsmentioning
confidence: 99%
“…In Iran, 24/7 primary percutaneous coronary intervention (PCI) as the standard treatment strategy for patients with ST-elevation myocardial infarction (STEMI) [3][4][5][6][7] was launched in September 2015 to achieve a fair distribution of healthcare resources. Currently, 49 general and heart hospitals provide these services, with 48 915 patients having undergone primary PCI thus far.…”
Section: Sirsmentioning
confidence: 99%
“…Early revascularization of the infarct-related artery is crucial to reduce myocardial damage and preserve myocardial function and the detrimental effects of treatment delay have been shown in many studies [ 17 , 18 ]. Single-stage multivessel PCI in STEMI patients without cardiogenic shock was not recommended in earlier STEMI guidelines based on adverse outcome with multivessel PCI reported by observational studies [ 4 , 19 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The dispatch priority code 2 causes a significant delay in reaching patients' location by METs and, consequently, results in the delayed restoration of coronary artery patency. 22 Clawson et al 23 showed that the dispatch priority code strongly influences the delay in the initiation of reperfusion therapy in patients with ACSs.…”
Section: What's New?mentioning
confidence: 99%